2013
DOI: 10.1039/c2cp43761a
|View full text |Cite
|
Sign up to set email alerts
|

Hydrophobic asymmetric ultrafiltration PVDF membranes: an alternative separator for VFB with excellent stability

Abstract: Polyvinylidene fluoride (PVDF) ultrafiltration membranes were investigated for the first time in vanadium redox flow battery (VFB) applications. Surprisingly, PVDF ultrafiltration membranes with hydrophobic pore walls and relatively large pore sizes of several tens of nanometers proved able to separate vanadium ions and protons efficiently, thus being suitable as a VFB separator. The ion selectivity of this new type of VFB membrane could be tuned readily by controlling the membrane morphology via changes in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
53
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 89 publications
(54 citation statements)
references
References 26 publications
0
53
0
1
Order By: Relevance
“…Just because of the specific characteristics of VRFB, the electrolytes, membrane, electrode in addition to the cell structure influence the battery performance jointly, especially for the former two determine the battery cost to a great extent [2]. Up to know, plenty of researchers devote themselves to the improvement in the membrane and electrolytes [3][4][5][6], and some of achievements have been successfully generalized in the engineering application of VRFB. However, as the continuous improvements in the membrane and electrolyte of VRFB, it is found that the relatively poor electrochemical activity of CF or GF seriously limited the electrochemical performance of VRFB, and the improvement in the electrochemical activity of electrode becomes an important problem worried to be solved [7][8].…”
Section: Introductionmentioning
confidence: 98%
“…Just because of the specific characteristics of VRFB, the electrolytes, membrane, electrode in addition to the cell structure influence the battery performance jointly, especially for the former two determine the battery cost to a great extent [2]. Up to know, plenty of researchers devote themselves to the improvement in the membrane and electrolytes [3][4][5][6], and some of achievements have been successfully generalized in the engineering application of VRFB. However, as the continuous improvements in the membrane and electrolyte of VRFB, it is found that the relatively poor electrochemical activity of CF or GF seriously limited the electrochemical performance of VRFB, and the improvement in the electrochemical activity of electrode becomes an important problem worried to be solved [7][8].…”
Section: Introductionmentioning
confidence: 98%
“…A few researchers have reported primary investigations into the use of porous membranes to separate protons and vanadium ions for VFB applications [10][11][12][13]. The pore structures of these porous membranes were mainly irregular finger-like or spongy micropores that were formed through conventional phase-inversion processes.…”
Section: Introductionmentioning
confidence: 99%
“…One of the major advantages VRBs offer over other flow batteries with different chemistries is their resistance to electrolyte cross-contamination, giving them a theoretically infinite lifespan. First pioneered by Skyllas-Kazacos at the University of New South Wales [1e3], research has mainly focused on electrode [4e9], electrolyte [10e12] and membrane treatment [13,14] in order to achieve high energy efficiencies.…”
Section: Introductionmentioning
confidence: 99%